PRODUCTION OF SOY MILK YOGURT AS A PLANT-BASED FUNCTIONAL FOOD USING MIXED CULTURES OF LACTOBACILLUS REUTERI AND STREPTOCOCCUS THERMOPHILUS - Emir Juliansyah, Muhammad
Plant-based milk yogurt, such as that made from soy, can be an alternative for individuals with vegan lifestyles and lactose intolerance. However, plant-based yogurt generally has organoleptic characteristics such as taste, aroma, and texture that are less favored by the public compared to conventional yogurt. Additionally, the absence of vitamin B12 in plant-based foods can cause health issues like anemia, weakness, fatigue, nausea, and dizziness. Therefore, efforts to create plant-based yogurt from soybeans need to be made using probiotic bacteria that produce vitamin B12, such as Lactobacillus reuteri. Furthermore, a mixed culture with Streptococcus thermophilus is used to enhance the taste, aroma, and texture to be more acceptable to the public as an alternative to animal yogurt. In this study, the optimization of incubation time and inoculum amount was carried out for the fermentation of soy milk yogurt with a mixed culture of lactic acid bacteria (Lactobacillus reuteri and Streptococcus thermophilus). Optimization of incubation time and inoculum amount was performed using the Response Surface Methodology (RSM). The response variables analyzed included cell count, pH, and organoleptic values. Then the optimal fermentation results were tested for vitamin B12 content using High Performance Liquid Chromatography (HPLC), antioxidant test using DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging assay, population dynamics analysis, probiotic viability test, and coliform contamination test. Based on the research results, the optimal fermentation results obtained through RSM were an incubation time of 13 hours with variations in the amount of inoculum of Lactobacillus reuteri culture 0.85 OD600nm 1% (v/v) and Streptococcus thermophilus 0.1 OD600nm 1% (v/v). The validation results obtained a final cell count of 1.54 x 10^8 CFU/mL, taste organoleptic value of 2.11, and aroma organoleptic value of 2.38. These three response variables fell within the range of 95% CI and 95% PI. For the product acceptance variable, a value of 3.3 was obtained, which is outside the range of 95% CI and 95% PI. The optimal fermentation results had a vitamin B12 content of 0.05 ppm. The antioxidant test using the DPPH scavenging assay showed an increase in antioxidant activity (% scavenging) after fermentation from 23.5% to 30.1%. The antioxidant activity value of the optimal fermentation results was equivalent to ascorbic acid 38.06 ppm. The probiotic viability test showed that probiotics could survive acidic conditions with a survivability percentage of 90% after 2 hours of incubation at pH 2.5. Based on the population dynamics analysis over 14 hours of fermentation of the optimal soy milk yogurt, faster growth was observed in L. reuteri with ?= 0.478 h?¹ compared to the growth of S. thermophilus with ? = 0.191 h?¹, and there was no growth pattern indicating interaction between the two bacteria. The coliform contamination test showed no coliform bacteria contamination in the final fermentation results. Therefore, it can be concluded from this study that fermentation using Lactobacillus reuteri and Streptococcus thermophilus can produce soy milk yogurt with good acceptance and nutritional content such as vitamin B12, antioxidants, and good probiotics that are safe for consumption.